# Find the Y-Intercept 10x+18y=24

10x+18y=24
Rewrite in slope-intercept form.
The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.
y=mx+b
Subtract 10x from both sides of the equation.
18y=24-10x
Divide each term by 18 and simplify.
Divide each term in 18y=24-10x by 18.
18y18=2418+-10×18
Cancel the common factor of 18.
Cancel the common factor.
18y18=2418+-10×18
Divide y by 1.
y=2418+-10×18
y=2418+-10×18
Simplify 2418+-10×18.
Simplify each term.
Cancel the common factor of 24 and 18.
Factor 6 out of 24.
y=6(4)18+-10×18
Cancel the common factors.
Factor 6 out of 18.
y=6⋅46⋅3+-10×18
Cancel the common factor.
y=6⋅46⋅3+-10×18
Rewrite the expression.
y=43+-10×18
y=43+-10×18
y=43+-10×18
Cancel the common factor of -10 and 18.
Factor 2 out of -10x.
y=43+2(-5x)18
Cancel the common factors.
Factor 2 out of 18.
y=43+2(-5x)2(9)
Cancel the common factor.
y=43+2(-5x)2⋅9
Rewrite the expression.
y=43+-5×9
y=43+-5×9
y=43+-5×9
Move the negative in front of the fraction.
y=43-5×9
y=43-5×9
Reorder 43 and -5×9.
y=-5×9+43
y=-5×9+43
y=-5×9+43
Rewrite in slope-intercept form.
y=-59x+43
y=-59x+43
Using the slope-intercept form, the y-intercept is 43.
b=43
Find the Y-Intercept 10x+18y=24

Scroll to top